Relaxin and the Cardiovascular System: from Basic Science to Clinical Practice - Martins, Rafael C.; Pintalhão, Mariana; Leite-Moreira, Adelino; Castro-Chaves, Paulo (Current Molecular Medicine, 2020)
The peptide hormone relaxin was originally linked to reproductive physiology, where it is believed to mediate systemic and renal hemodynamic adjustments to pregnancy. Recently, its broad range of effects in the cardiovascular system has been the focus of intensive research regarding its implications under pathological conditions and potential therapeutic potential. An understanding of the multitude of cardioprotective actions prompted the study of serelaxin, recombinant human relaxin-2, for the treatment of acute heart failure. Despite early promising results from phase II studies, recently revealed RELAX-AHF-2 outcomes were rather disappointing and the treatment for acute heart failure remains an unmet medical need. This article reviews the physiologic actions of relaxin on the cardiovascular system and its relevance in the pathophysiology of cardiovascular disease. We summarize the most updated clinical data and discuss future directions of serelaxin for the treatment of acute heart failure. This should encourage additional work to determine how can relaxin's beneficial effects be exploited for the treatment of cardiovascular disease.
Keywords: cardiovascular drugs